Ponorogo Regency Green Open Space Analysis of Law Number 27 of 2007 concerning Spatial Planning - Arimurti, Danang Johar; Najicha, Fatma Ulfatun (Universitas Negeri Semarang, 2023)
One of the uses of space stated in Law Number 26 of 2007 concerning Spatial Planning is Green Open Space (RTH). This law requires that each district/city have a green open space area of at least 30% of the entire regional area. Ponorogo Regency is one of the districts in East Java Province which has an area of 137,178 Ha. This research will discuss the suitability of the green open space owned by Ponorogo Regency to Law Number 26 of 2007 concerning spatial planning and the potential for developing green open space in the Ponorogo Regency area. This article uses normative research methods with a positive legal approach and an approach using statistical data. The result is that Ponorogo Regency has not yet reached the minimum green open space limit of 30% because it is still at 19%. However, Ponorogo Regency has ambitions with the existence of Regional Regulation Number 1 of 2012 concerning RTRW 2012-2032 which states that the minimum limit of 30% RTH will be achieved in 2032. For the potential for developing RTH areas, Ponorogo Regency has three places, namely roads, river routes and mining areas.